Tinjauan Yuridis Filosofis Eksistensi Kearifan Lokal - Zainul Akmal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
This study aims to determine the relationship between local wisdom and indigenous peoples and the dependence of local wisdom on its creators at the level of application. It was found that local wisdom is partly produced by indigenous peoples and partly produced by non-indigenous people. Local wisdom is also not carried out in its application with its creator, because local wisdom and universal values ​​can be transformed or inherited or learned by anyone, so that it can be applied by anyone.